Inactivated Influenza Vaccination for People With Spinal Cord Injury - Trautner, Barbara W. (2004)
OBJECTIVE: To examine the antibody responses of people with spinal cord injury (SCI) to the commercially available trivalent influenza vaccine. DESIGN: Prospective trial of patients and controls. SETTING: Veterans Affairs medical center. PARTICIPANTS: Forty people with SCI and 40 able-bodied subjects. INTERVENTION: Intramuscular administration of inactivated influenza vaccine. MAIN OUTCOME MEASURES: Antibody responses were determined by using the standard hemagglutination-inhibition test before and 4 weeks after vaccination. Serum antibody responses were assessed as follows: (1) percentage of each cohort achieving a 4-fold or greater rise in antibody titer, (2) percentage of each cohort achieving a postvaccination antibody titer of 32 or more, and (3) postvaccination geometric mean antibody titers. RESULTS: The serum antibody responses to each vaccine antigen were similar for the SCI and the control cohorts for the 3 outcomes. Neither the time since injury (≤1y vs >1y) nor the level of injury (paraplegia vs quadriplegia) affected the vaccine antibody responses in the SCI cohort. Subjects older than 65 years had lower postvaccination serum antibody levels than those younger than 65 years (P<.05). CONCLUSIONS: People with SCI responded to influenza vaccination in a manner similar to able-bodied subjects and would be expected to benefit from vaccination.